Profile Patient In Patient Schizophrenia In House Special Illnesses In The Dadi Makassar Region - Qurniawati, Qurniawati; Irma Santy; A. Suheyra Syauki; Uyuni Aziz; Hawaidah, Hawaidah (Jurnal EduHealth, 2024)
Mental disorders are diseases caused by disturbances in an individual's thoughts, perceptions and behavior No able to adapt yourself with self Alone, person others, society and the environment. Schizophrenia is the most common mental disorder in Indonesia. To find out Profile of Schizophrenia Patients Inpatient at Dadi Makassar Regional Special Hospital. This research was conducted using a retrospective approach with descriptive methods using secondary data from the Dadi Makassar Regional Special Hospital and analyzed using Excel. Sample selection using simple random sampling of patients diagnosed with schizophrenia. There were 91 samples of schizophrenia sufferers at RSKD Dadi Makassar. Most schizophrenia patients were in the age range of 36-45 years with 35 patients (38%). Patients were dominated by male patients 76 (84%). The highest level of education was at the high school level, 36 patients (40%). Patients who had jobs were 58 (64%). Most patients came from the Bugis tribe, 44 (48%). There were 31 patients (34%) who had a family history of mental disorders. The most common type of schizophrenia patient was YTT schizophrenia, namely 84 patients (92%). There were 72 patients who had suffered from schizophrenia for more than 2 years (79%). There were 46 patients who had undergone schizophrenia treatment for less than 2 years (51%). The time to start treatment in schizophrenia patients was greater when symptoms had been felt for less than 2 years, as many as 52 patients (57%). There were 2 patients (2%) who had a history of drug use. BPJS users were 81 patients (89%).